Finitistic Spaces in Intuitionistic Fuzzy Topological Spaces - AbdulGawad A. Q. Al-Qubati (International Journal of Mathematics And its Applications, 2023)
In this paper the concept of intuitionistic fuzzy finitistic space is introduced by means Q-cover of intuitionistic fuzzy open sets. Some interesting results are obtained.